The use of geographic information systems to measure the financial performance of micro enterprises - Lau, Elfreda Aplonia; Endayani, Sri; Kulsum, Umi; Stefano, Andrew; Rokhim, Abdul; Purbawati, Purbawati (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
This study examines the application of geographic information systems (GIS) to measure and visualize the financial performance of micro enterprises in remote areas of East Kalimantan, Indonesia. Micro enterprises are crucial to local economies but often face barriers such as limited capital access, inadequate infrastructure, and insufficient business training. Using a mixed-method approach, the research combined surveys of 200 micro business owners, secondary economic data, and GIS-based spatial analysis. The results indicate clear spatial disparities: enterprises located closer to financial institutions and training programs achieved 25–30% higher profitability and stronger operational resilience. GIS mapping effectively identified performance clusters and underserved zones, providing actionable insights for targeted policy interventions. Key factors influencing financial outcomes include access to capital, training opportunities, and infrastructure quality. This study demonstrates the value of GIS as a decision-support tool for policymakers in designing spatially informed financial assistance, infrastructure planning, and mobile training deployment. The findings contribute to socio-economic planning discourse and propose a replicable GIS-based framework for strengthening microenterprise resilience in underdeveloped regions.